Analisis Abnormal Return Dan Trading Volume Activity Sebelum Dan Sesudah Pengumuman Kenaikan Suku Bunga Oleh The FED (Studi Kasus Pada Perusahaan Yang Terdaftar Indeks LQ-45 di BEI) - Alif Sholahudin Sumantri; Ronny Malavia Mardani; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This event study research aims to analyze international events and their impact on the Indonesian capital market. The event studied was the announcement of the interest rate hike made by the Central Bank of the United States (The FED) on May 3-4, 2022. The study analyzed abnormal returns and trading volume activities created during the event. The observation period carried out in this study was five days before and five days after. The population in this study is the companies listed in the index LQ45. The analysis technique used in this study is the Paired Sample t-test. The results showed a significant difference in abnormal returns before and after and abnormal positive returns after the announcement of the fed’s rate hike. And there is a significant difference in trading volume activity before and after, and an increase in trading volume activity after the announcement of the fed’s rate hike. Keywords: Event Studies, Abnormal Returns, Trading Volume Activity, And Interest Rates.